Examining the current value of indigenous plant material culture in Limpopo Province, South Africa - Rankoana, Sejabaledi A. (Technium Social Sciences Journal, 2021)
Indigenous plant-derived material culture dominates many of the tools and utensils manufactured and used by communities that depended on the natural resources for their livelihoods. Endemic plants provide humans with essential materials for construction purposes and for the design of household utensils. The goal of this study was to describe the current value of indigenous plant material culture. Semi-structured interviews with a purposive sample of 127 respondents provide 13 native plants as sources of fibre, timber, culms, oil and dye used to make household utensils, huts, brooms, mats and baskets. The cultural significance of these materials includes the production, preparation, serving and storage of food; house construction; protection of courtyards; and cleaning. These materials are still valued in the culture of the studied community, and represent the tangible heritage of the community.